Understanding of Consciousness as object of study and practice in psychology and education: Contributions of Freire and Vygotsky (Revista de Psicología, 2020)
The dialogicity between the creative work of L.S. Vygotsky and Paulo Freire's has been a topic of interest to me for more than two decades. That dialogicity is particularly notable with regard to the issue of consciousness. However, the literature examining this subject, its background and its implications for psychology and education is scarce. This article is an attempt to help remedy that situation. It aims to analyze the place of consciousness in the work of both authors and the implications that their conceptions on the origin and development of consciousness development have for psychology and education.
Keywords: Vygotsky; Freire; consciousness; psychology; education